Livestock and Livelihoods in Rural Tanzania : A Descriptive Analysis of the 2009 National Panel Survey - Covarrubias, Katia; Nsiima, Longin; Zezza, Alberto (World Bank, Washington, DC, 2014)
In 2006, the government approved a national livestock policy based on the premise that the livestock industry has an important role to play in building a strong national economy and in the process, reducing inequalities among Tanzanians by increasing their incomes and employment opportunities. This report presents an analysis of rural livelihoods in Tanzania, with particular emphasis on the livestock sub-sector, smallholder farmers' living standards, and issues with access to productive assets. The report attempts to answer basic questions such as: to what extent is keeping livestock an activity of the relatively better off, and to what extent are poorer households able to engage?; how does the role of livestock vary with different levels of income and well-being?; how are livestock holding size and structure associated with differences in welfare, gender, and geography?; how important are input and output markets for small livestock keepers?; what form does this market participation take in practice, and to what extent?; and to what extent do the non-income services of livestock (for example, manure, draught power) benefit crop production? The study is based on data from the Tanzania national panel survey (NPS) collected by the national bureau of statistics (NBS) from October 2008 to October 2009 as part of the first wave of a nationally representative living standards survey. Data was collected using household, agricultural, and community questionnaires in which information was obtained at the individual, household, plot, and community level The report is organized as follows: section one gives background information; description of the data is presented in section two, in section three the authors analyze the composition of rural income, household endowment of human capital, and access to infrastructure and assets, in order to gain an understanding of the level of wellbeing in the rural space. A descriptive analysis of the characteristics of small rural livestock owners and their production practices is provided in section four, which highlights the heterogeneity of the households engaged in the livestock sector and presents evidence of the sector's importance to rural livelihoods in terms of both income and consumption. Section five concludes with a discussion of key results and their implications for policy and further analysis.